Wear mechanisms description in nanoscale by SEM/TEM of multilayer Zr/ZrN coatings in dependence on phases ratio. (10th October 2022) - Major, L.; Lackner, J. M.; Kot, M.; Major, R.; Dyner, M.; Major, B.
Abstract: As a result of loading with an external force during the wear process, coating deforms uniformly. After a certain limit load is exceeded, coating deformation is localised through the formation of the so‐called shear bands. It has been showed experimentally the process of shear bands formation. The microstructural characterisation before and after the mechanical tests was performed using scanning and transmission electron microscopy (SEM and TEM) on cross‐sections of the samples. The analysis indicated that in the case of multilayer coatings where the ratio of the metallic to the ceramic phase is 1:1, the shear bands are formed at an angle of 45°. With a greater proportion of the ceramic phase to metallic (ratio 1:2), the shear band changed the shear angle from ∼45° to ∼90°. Mechanical in situ tests were carried out in the chambers of SEM and TEM. The scratch tests in the SEM were done with the simultaneous observation of the phenomena occurring on the surface of the tested materials showed that at a scratch force of 0.04 N, the additional outer a‐C:H layer was damaged, which was shown in the form of a fault in the force–displacement diagram, and in the form of splits visible in the SEM image. However, the application of this additional layer had a positive effect on the wear mechanism of the entire coating structure. The test also indicated that in the case of coatings with phases ratio 1:2 and 1:4 (metallic to ceramic), the characteristics of the brittle material were demonstrated, unlike the coating with a 1:1 phase ratio, where plastic properties predominated. However, for the 1:2 phase ratio coating, the chip was more ductile than for the chip formed when testing a 1:4 phase ratio coating. For in situ mechanical testing in the TEM, a straining holder was used. The test showed that the shear band angle for a 1:1 ratio coating has changed from 45° to 90° due to the different direction of force interaction.